Entomophthoromycosis in Maharaj Nakorn Chiang Mai Hospital - Chiewchanvit S. (2014)
Objective: To review documented entomophthoromycosis patients at Maharaj Nakorn Chiang Mai Hospital from 1985 to 2001. Material and Method: A retrospective review was performed at Maharaj Nakorn Chiang Mai Hospital from 1985 to 2001. Eight cases of entomophthoromycosis were found between 1988 and 1993, with five patients diagnosed as subcutaneous zygomycosis, 1 GI entomophthoromycosis and 2 rhinofacial zygomycosis. Results: The subcutaneous zygomycosis group was composed of 5 female patients, aged 7-77 years. They presented with a painless subcutaneous mass, which was solitary or multiple and most commonly found on the extremities. The duration of disease was between 3 months to 5 years. The cultures grew Basidiobolus ranarum. A case of GI entomophthoromycosis was seen in a 34 year old man, who presented with dyspepsia, multiple intraabodminal masses and peritonitis. Two cases of conidiobolomycosis (rhinofacial zygomycosis) were seen. These two patients were male, 26 and 39 years old, and they presented with unilateral nasal obstruction from a mass at the inferior turbinate. The cultures grew Conidiobolus coronatus. Conclusion: Entomophthoromycosis in the northern part of Thailand is rare. The disease should be differentially diagnosed by a chronic painless tumor. The patients in this review responded very well to the recommended therapy.